Muscular strength, neuromuscular activation and performance in discus throwers - Karampatsos, G.; Terzis, G.; Georgiadis, G. (Journal of Physical Education and Sport, 2011)
The aim of the study was to investigate muscular strength and neuromuscular activation of the lower extremities during discus throwing. Six experienced, right-handed, discus throwers, performed three maximal attempts from the power position and three maximal attempts with the full rotational style. They also performed a maximum squat and incline bench press test. Electromyographic (EMG) signals were recorded from quadriceps and gastrocnemius of the right and the left lower extremities during all efforts. Average EMG signals (aEMG) during discus throwing were normalized relatively to the EMG signals measured during 1RM squat strength test. Discus throwing performance, was significantly correlated with 1RM in incline bench press (r=0.96, p<0.01) as well as with aEMG from right quadriceps, at the delivery phase (r=0.81, p<0.05). Discus throwing performance was significantly, negatively, correlated with the duration of the activation of quadriceps and gastrocnemius of right lower extremity (r=-0.94, p<0.01, and r=-0.88, p<0.05, respectively). These results suggest that discus throwing performance is strongly linked with absolute muscular strength during incline bench press but not with max squat strength. Furthermore, discus throwing performance seems to be strongly linked with an enhanced activation of the right quadriceps, as well as with a short activation of right quadriceps and gastrocnemius, during delivery.